Toxoplasma gondii Type-I ROP18 Targeting Human E3 Ligase TRIM21 for Immune Escape - Yao, Lijie; Xu, Liqing; Zhou, Lijuan; Wu, Shuizhen; Zou, Weihao; Chen, Min; Chen, Jiating; Peng, Hongjuan (Frontiers in Cell and Developmental Biology, 2021)
Toxoplasma gondii is an intracellular pathogen that exerts its virulence through inhibiting host’s innate immune responses, which is mainly related to the type II interferon (IFN-γ) response. IFN-γ inducible tripartite motif 21 (TRIM21), an E3 ligase, plays an important role in anti-infection responses against the intracellular pathogens including bacteria, virus and parasite. We found that T. gondii virulence factor ROP18 of the type I RH strain (TgROP18I) interacted with human TRIM21, and promoted the latter’s phosphorylation, which subsequently accelerated TRIM21 degradation through lysosomal pathway. Furthermore, TRIM21 protein level was found to be upregulated during RH and CEP infection. TRIM21 knocking down reduced the ubiquitin labeling on the PVM (which led to PV acidification and death of CEP tachyzoites), and relieved the inhibition of CEP proliferation induced by IFN-γ in HFF cells which was consistent with the result of TRIM21 overexpression. On the other hand, TRIM21 overexpression enhanced the inhibition of CEP proliferation, and inhibited the binding of IκB-α with p65 to activate the IFN-γ-inducible NF-κB pathway, which might be resulted by TRIM21-IκB-α interaction. In brief, our research identified that in human cells, IFN-γ-inducible TRIM21 functioned in the innate immune responses against type III T. gondii infection; however, TgROP18I promoted TRIM21 phosphorylation, leading to TRIM21 degradation for immune escape in type I strain infection.